IDENTIFIKASI KAPANG PADA IKAN TERBANG (Hirundichthys oxycephalus) ASIN DI PASAR BERSEHATI - Jumalia, Jumalia; Agustin, Agnes Triasih; Lohoo, Helen Jenny (Media Teknologi Hasil Perikanan, 2014)
The aim of this study was to identify the mold of salted flying fish (Hirundichthys oxycephalus) at pasar Bersehati Manado. The aim Manado this study was to identified the mold of salted Flying fish at pasar Bersehati Manado. These research was carried out chemical analysis and microbial analysis of salted fish in two steps which are the total plate colony and identified the species of mold. The chemical analysis was persentase of water content and pH. The result showed that the water content of the flying fish was 29.33–37.00% and pH was 7.24–7.37. And the result of the microbial test showed that total colony of mold was 7x102–13.1x103 CFU/gram and the spesies were Fusarium sp and Aspergillus sp.Keywords: flying fish, salted, microbial, Manado.